(untitled) (BIRDEM Medical Journal, 2018)
Background: The prevalence of diabetes mellitus is increasing throughout the world, mostly type 2 diabetes mellitus and largely contributed by increasing body mass index (BMI). This study was designed to compare BMI of newly detected diabetic patients in two different Bangladeshi cohorts spaced over 25 years. Methods: This was a retrospective study from hospital records from two cohorts: 1981 to 1985 and 2006 to 2010. Patients were divided in 4 groups according to BMI and comparison was made. BMI of newly detected diabetic patients from 2011 and 2012 were also compared. Results: Age at diagnosis of diabetes was lower in 2006-2010 group than 1981-1985 group. Frequency of diabetes at lower BMI has fallen by half in 2006-2010 group when compared with those of 1981-1985 group. Frequency of diabetes at higher BMI groups has an increasing trend in 2006-2010 group than in 1981-1985 group. Conclusion: Results from this study concludes that there is an increasing trend of diabetes detection at lower age group and with higher BMI among Bangladeshi population. Birdem Med J 2018; 8(2): 99-102